Integration of CT and MRI imaging with plastination for enhanced veterinary anatomy education: a study on the crab-eating fox (Cerdocyon thous) - Alcobaça, Mayla Magalhães de Oliveira; Bittencourt, Athelson Stefanon; Monteiro, Yuri Favalessa; Chaim, Khallil Taverna; Banhos, Aureo; Assis Neto, Antônio Chaves de (Frontiers in Veterinary Science, 2025)
IntroductionWith the advancements in diagnostic imaging and its increasing use in veterinary medicine, it is essential for professionals to continuously update their knowledge and seek training in the anatomy of various wild animal species. Plastination allows for the preservation of biological tissues and their anatomical details, enhancing the study and identification of structures.MethodsThis study aimed (1) to describe in detail the anatomy of the thoracic and pelvic limbs of the crab-eating fox (Cerdocyon thous) using plastinated metameric sections correlated with computed tomography (CT) and magnetic resonance imaging (MRI), and (2) to analyze tissue shrinkage resulting from plastination. Limbs from four animals of both sexes were scanned using CT and MRI, and the resulting images were saved in DICOM format. The limbs were then plastinated using the silicone technique with forced impregnation at −18 °C, including fixation, dehydration, impregnation, and curing. Measurements of weight, thickness, and volume were taken before dehydration and after curing to assess shrinkage. Three-dimensional reconstructions and multiplanar virtual dissections were also performed to identify and describe anatomical structures.ResultsThe study enabled detailed identification and description of anatomical structures in plastinated transverse sections and their correlation with corresponding axial CT and MRI images, as well as the 3D reconstruction of the limbs for anatomical correspondence with each sectioned region. Qualitatively, the specimens showed excellent preservation of anatomical features, allowing for clear visualization and identification of structures while maintaining their syntopic relationships. The plastinated material was rigid, easy to handle, odorless, and free from toxic characteristics. Quantitative analysis demonstrated minimal shrinkage in the plastinated tissues.DiscussionPlastinated metameric sections of the thoracic and pelvic limbs of Cerdocyon thous, when correlated with CT and MRI, proved to be an effective tool for anatomical studies. This integrated approach improves anatomical understanding, supports the interpretation of imaging studies, enhances educational resources, and benefits veterinary professionals in both anatomy and diagnostic imaging. The minimal tissue shrinkage observed did not compromise the quality or anatomical integrity of the specimens.